2014
DOI: 10.1007/s10103-014-1562-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the use of LED phototherapy on bone defects grafted with hydroxyapatite on rats with iron-deficiency anemia and nonanemic: a Raman spectroscopy analysis

Abstract: This study aimed to assess bone repair in defects grafted or not with hydroxyapatite (HA) on healthy and iron-deficiency anemia (IDA) rats submitted or not to LED phototherapy (LED-PT) by Raman spectroscopy. The animals were divided in eight groups with five rats each: Clot; Clot + LED; IDA + Clot; IDA + LED; Graft; Graft + LED; IDA + Graft; and IDA + Graft + LED. When appropriated, irradiation with IR LED (λ850 ± 10 nm, 150 mW, CW, Φ = 0.5 cm(2), 16 J/cm(2), 15 days) was carried out. Raman shifts: ∼ 960 [symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
0
12
0
3
Order By: Relevance
“…O avanço nas técnicas laboratoriais em análises clínicas é de grande necessidade, uma vez que permitirá a minimização de alíquota coletada, com os riscos biológicos ocupacionais, minimização de custos de análise, conscientização ambiental e rapidez e precisão analítica. Em estudo recente 25 , foi observado que o uso de tecnologias limpas de análise, como a espectroscopia no infravermelho com transformada de Fourier (do inglês, Fourier transform infrared spectroscopy -FT-IR), associada aos métodos de análise multivariada, é capaz de detectar alguns fungos como a Candida sp. a partir de pouca biomassa.…”
Section: Fototerapia: Um Panorama Das Aplicações Da Luz Em Diversos Punclassified
“…O avanço nas técnicas laboratoriais em análises clínicas é de grande necessidade, uma vez que permitirá a minimização de alíquota coletada, com os riscos biológicos ocupacionais, minimização de custos de análise, conscientização ambiental e rapidez e precisão analítica. Em estudo recente 25 , foi observado que o uso de tecnologias limpas de análise, como a espectroscopia no infravermelho com transformada de Fourier (do inglês, Fourier transform infrared spectroscopy -FT-IR), associada aos métodos de análise multivariada, é capaz de detectar alguns fungos como a Candida sp. a partir de pouca biomassa.…”
Section: Fototerapia: Um Panorama Das Aplicações Da Luz Em Diversos Punclassified
“…We highlight the laser light used for laser phototherapy (LPT). Over the past 20 years, experimental protocols have been proposed for a considerable number of procedures involving bone repair in animals and humans [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. These protocols are now also used as an aid to an efficient repair of mineralized tissues, as LPT accelerates bone repair by directly affecting, in different ways, the new bone formation.…”
Section: Laser In Dentistrymentioning
confidence: 99%
“…Fibroblast proliferation and its increased activity have been previously detected in individuals and cultures of irradiated cells and are responsible for the high concentration of collagen fibers observed in the irradiated bone. Our previous studies indicate that the effective result of LPT is observed when the treatment is performed in the initial stages of repair, when a large cell proliferation occurs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Vascular responses to LPT have also been suggested as one of the possible mechanisms responsible for the positive clinical results observed.…”
Section: Laser In Dentistrymentioning
confidence: 99%
See 2 more Smart Citations